Primary Pterygium Excision with Amniotic Membrane Grafting among Rural Eye Patients in Bangladesh - Matin , Md Abdul; Shahin, Mahbubur Rahman; Nawreen, Tasnia; Sara, Mubashera (The Journal of Ad-din Women’s Medical College, 2023)
Objective: Since treatment of pterygium by topical and systemic medications is not effective, surgical treatment remains the only way to resolve the problem. This study was therefore aimed to evaluate the outcome of primary pterygium excision with amniotic membrane graft among patient with eye diseases in rural Bangladesh. Methodology: This study was conducted at the Pangsha Eye Hospital of District Rajbari among a total 280 pre-selected eye patients having primary pterygium over the period of 7 years (January 2012-June 2019). Surgical excision was performed with transplantation of preserved amniotic membrane on to the bare sclera. Every patient was followed up for at least next 6 months. Results: The results were evaluated in terms of recurrent pterygium growth and related complications. Of total 280 patients, pterygium was excision both of 138 (49.29%) being male and 142(50.71%) being female with mean ages of 43.36±10.88. The pterygium extended on to the corneas for 4.76±1.4 mm (range 3 to 8) mm. Only 11(4%) eyes demonstrated recurrent pterygium. Seven of them were male and 4 were female which was managed by second grafting leading to complete resolution. Of various complications, mild hematoma was observed in 3 cases, and, in 2 cases were had mild sclera dryness in bare scleral area after pterygium excision which were managed by topical steroid and artificial tear. Conclusion: Findings of this study yielded that primary pterygium excision with amniotic membrane transplantation is remains a safe and effective surgical technique with minimum recurrence rate. The Journal of Ad-din Women's Medical College; Vol. 11 (1), Jan 2023; p 4-13